A Study of Customer Satisfaction towards Hotel Industry in Kashmir valley - Misra, Lalat Indu; Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Customer satisfaction is the key role in supporting every company in the current competitive period. Service providers must consider their clients and develop their offerings in such a manner that the consumer enjoys the highest value possible. The goal of this study is to assess customer loyalty in Kashmir Valley Hotels. The research will also provide the consumers with varied ideas to render their services more effective and efficient. A well-planned Questionnaire is used for administering the survey to gather primary data from the respondents. The sample size for the analysis is 150 Sample range, and measures of conviction are used sample size calculation. The researcher followed simple random sampling methodology to collect the results. Based on the results, 42 percent of respondents are extremely pleased with the hotel's management and protection while 20 percent are strongly unhappy with the hotel's venue. With each feature, the degree of satisfaction varies, making it clear with every single attribute, and consumers perceive their loyalty differently. Ultimately, it has been established that the hotels ' customer satisfaction is high.